2017
DOI: 10.1007/978-981-10-6583-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Role of DJ-1 in Fertilization

Abstract: Neither a sperm nor an egg can develop into an individual alone. Only when the sperm and egg bind and fuse, which is known as fertilization, can they acquire the ability of developing into new individuals. DJ-1 was reported to be involved in the process of fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Indeed, the majority of human cancers overexpress DJ-1 mRNA [28] and it is highly expressed in testicles, all of which are high-energy demand tissues characterized by a high glycolytic flux. Indeed, decreased expression of DJ-1 in sperm and epididymides correlates with male infertility [29,30]. DJ-1 protein levels also increase in human islets of Langerhans beta cells upon exposure to high glucose concentrations, indicating a protective role for DJ-1 in this cell type [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the majority of human cancers overexpress DJ-1 mRNA [28] and it is highly expressed in testicles, all of which are high-energy demand tissues characterized by a high glycolytic flux. Indeed, decreased expression of DJ-1 in sperm and epididymides correlates with male infertility [29,30]. DJ-1 protein levels also increase in human islets of Langerhans beta cells upon exposure to high glucose concentrations, indicating a protective role for DJ-1 in this cell type [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…It can enhance the hypothalamic-pituitary-adrenal function and promote the release of relevant transmitters and hormones in vivo to play the role of tonifying kidney essence, and also has the role of protecting cerebral ischemia. Other studies have shown that [11], cistanche total glycosides can protect cerebral ischemia and cerebral ischemia-reperfusion injury. Animal experiments showed that it can protect cerebral ischemia and cerebral ischemia reperfusion injury by decreasing stroke index, percentage of cerebral infarction area, malondialdehyde content and nitric oxide synthase activity in brain tissue, and increasing superoxide dismutase activity in brain tissue.…”
Section: Modern Pharmacological Researchmentioning
confidence: 91%
“…Another protein implicated in PD pathogenesis is DJ-1, a small, dimeric protein that is most highly expressed in cells with high energy demands, such as neurons. Cells with high energy demand typically have high levels of reactive oxygen species, and one function of DJ-1 is to protect cells from oxidative stress (Wagenfeld et al, 1998;Kinumi et al, 2004;Taira et al, 2004;Kim et al, 2005;Meulener et al, 2005;Wilson, 2011;Jain et al, 2012;Ottolini et al, 2013;Batelli et al, 2015;Chunna and Pu, 2017;Eberhard and Lammert, 2017;Kawate et al, 2017;Kiss et al, 2017;Smith and Wilson, 2017;Catazaro et al, 2018). DJ-1 has also been implicated to act as a chaperone, modulating the toxicity and misfolding of both α-synuclein and mutant huntingtin (Batelli et al, 2008;Wang et al, 2011;Sajjad et al, 2014;Zondler et al, 2014).…”
Section: Dj-1mentioning
confidence: 99%